PERIODONTITIS AS A MANIFESTATION OF SYSTEMIC DISEASES: BASIC CONCEPTS - Soares, Kaio Henrique; Martins, Olga Beatriz Lopes; Leite, Mariana Botelho; Alves, Sâmia Francy Ferreira; Lopes, Maria Rita Lima; Santos, Jefferson Aguiar; Paulino, Gabriela Leite; Soares, Célio Leone Ferreira; Santos, Carolina Carvalho de Oliveira (Seven Editora, 2026)
Periodontitis as a manifestation of systemic diseases represents a condition in which systemic alterations directly influence the susceptibility, progression, and severity of periodontal destruction. This chapter discusses the inflammatory mechanisms involved in periodontitis, highlighting the participation of pro-inflammatory cytokines, prostaglandins, metalloproteinases, and the RANK/RANKL/OPG system in alveolar bone loss. Furthermore, it addresses the relationship between systemic diseases—such as diabetes mellitus, leukemia, HIV/AIDS, genetic syndromes, autoimmune diseases, and immunological disorders—and their periodontal repercussions. The 2017 classification reinforces the importance of recognizing these systemic manifestations in periodontal diagnosis, emphasizing the need for a multidisciplinary approach, based on detailed anamnesis, clinical, radiographic, and laboratory examinations, for comprehensive and individualized patient management.